PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN PRESTASI BELAJAR SISWA KELAS VIII C SMP NEGERI 1 ELAR PADA MATERI LINGKARAN TAHUN PELAJARAN 2020/2021 - Yuliani Yasinta Kurniati; Putu Suarniti Noviantari; Kadek Adi Wibawa (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Unmas Denpasar, 2022)
ABSTRACT This study aims to determine how much increase in student activity and achievement through the application of Number Head Together (NHT) cooperative learning in Circle learning in class VIII C of SMP Negeri 1 Elar in 2020/2021. This study uses a qualitative approach, this type of research is a classroom action research (CAR), Kurt Lewin. Data were collected using student learning outcomes, student test results to obtain qualitative data. The increase in learning activities and student achievement achieved as follows: (1) The increase in student learning activities is indicated by an increase in the category of student learning activities from the